2022
DOI: 10.33448/rsd-v11i12.34203
|View full text |Cite
|
Sign up to set email alerts
|

Fashion Industry 4.0: A Bibliometric Review in the Fashion Industry

Abstract: The fourth industrial revolution, or Industry 4.0 is characterized as information technology enabling complete digital connectivity, bringing together modern human life's physical, digital, and organic elements. In the competitive world of clothing, fashion and footwear, integrated technologies are constantly advancing, and the fashion industry needs to adapt to market standards. Given the above, this research aimed to search the literature in a bibliometric way on the evolution of the current situation of ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
(39 reference statements)
0
0
0
Order By: Relevance
“…Fiziksel yaşantıda, ağırlıklı olarak tasarım ve üretim yönünde, "geleneksel moda" olarak bildiğimiz pratikleri radikal bir tutumla dönüştürmektedir (Sharma, Koehl, Bruniaux, Zeng, & Wang, 2021). Bu dönüşümleri kategorize etmek ve kısaca özetlemek gerekirse (Oliveira, Näas, & Garcia, 2022):…”
Section: Geleneksel Moda üZeri̇nde Di̇ji̇tal Modanin Etki̇si̇unclassified
“…Fiziksel yaşantıda, ağırlıklı olarak tasarım ve üretim yönünde, "geleneksel moda" olarak bildiğimiz pratikleri radikal bir tutumla dönüştürmektedir (Sharma, Koehl, Bruniaux, Zeng, & Wang, 2021). Bu dönüşümleri kategorize etmek ve kısaca özetlemek gerekirse (Oliveira, Näas, & Garcia, 2022):…”
Section: Geleneksel Moda üZeri̇nde Di̇ji̇tal Modanin Etki̇si̇unclassified
“…Once a block is added to the chain, it is almost impossible to alter previous transactions [14]. This feature is particularly relevant in zakat management, where the integrity of financial records is crucial to maintaining public trust [15].…”
Section: Blockchain Technologymentioning
confidence: 99%
“…The results of the study [20,22] showed that Industry 4.0 contributes to the further development of digital technologies and tools of the fashion industry, which creates a fertile basis for improving customer relationships. Industry 4.0 resources have had a positive impact on apparel design and manufacturing, offering advancements in industries related to sustainable manufacturing [22].…”
Section: Features Of the Fashion Industry Transformational Processesmentioning
confidence: 99%